Single-route delaminated clay composites for efficient visible-light photo-mineralization of antibiotic-resistant bacteria and associated genes in water - (:unkn) unknown (My University, 2021)
Drinking water contaminated with antibiotic resistance bacteria could result in loss of antibiotic effectiveness in humans, increased healthcare cost and ultimately death. New delaminated photocatalytic composite (DPC) has been prepared. DPC (2g) doped with Cu/Zn kept multidrug resistant (MDR) E. coli and its sulphonamide resistance genes in contaminated water at Log reduction >6 for 36 h in 1st and 2nd disinfection steps under visible-light using fixed-bed mode (downward flow). In contrast, fluoroquinolone resistance genes persisted in treated water after first disinfection step and were significantly reduced after the second disinfection step. No bacteria re-growth was observed in treated water stored in light/dark for 7 days. A 95% photo-mineralisation of MDR E. coli and its genes in water was achieved via the release of superoxide radical (in dark and light). Shelf-life study of DPC vs non-delaminated photocatalytic composites over 7 month suggests that the former remained far efficient than the latter.
Keywords: African Research